Biomechanical Analysis of an Arthroscopic Broström Ankle Ligament Repair and a Suture Anchor–Augmented Repair. (July 2015) - Giza, Eric; Whitlow, Scott R.; Williams, Brady T.; Acevedo, Jorge I.; Mangone, Peter G.; Haytmanek, C. Thomas; Curry, Eugene E.; Turnbull, Travis Lee; LaPrade, Robert F.; Wijdicks, Coen A.; Clanton, Thomas O.
Background: Secondary surgical repair of ankle ligaments is often indicated in cases of chronic lateral ankle instability. Recently, arthroscopic Broström techniques have been described, but biomechanical information is limited. The purpose of the present study was to analyze the biomechanical properties of an arthroscopic Broström repair and augmented repair with a proximally placed suture anchor. It was hypothesized that the arthroscopic Broström repairs would compare favorably to open techniques and that augmentation would increase the mean repair strength at time zero. Methods: Twenty (10 matched pairs) fresh-frozen foot and ankle cadaveric specimens were obtained. After sectioning of the lateral ankle ligaments, an arthroscopic Broström procedure was performed on each ankle using two 3.0-mm suture anchors with #0 braided polyethylene/polyester multifilament sutures. One specimen from each pair was augmented with a 2.9-mm suture anchor placed 3 cm proximal to the inferior tip of the lateral malleolus. Repairs were isolated and positioned in 20 degrees of inversion and 10 degrees of plantarflexion and loaded to failure using a dynamic tensile testing machine. Maximum load (N), stiffness (N/mm), and displacement at maximum load (mm) were recorded. Results: There were no significant differences between standard arthroscopic repairs and the augmented repairs for mean maximum load and stiffness (154.4 ± 60.3 N, 9.8 ± 2.6 N/mm vs 194.2 ± 157.7 N, 10.5 ± 4.7 N/mm, P = .222, P = .685). Conclusions: Repair augmentation did not confer a significantly higher mean strength or stiffness at time zero. Clinical Relevance: Mean strength and stiffness for the arthroscopic Broström repair compared favorably with previous similarly tested open repair and reconstruction methods, validating the clinical feasibility of an arthroscopic repair. However, augmentation with an additional proximal suture anchor did not significantly strengthen the repair.